TYPE-1 DIABETES MELLITUS PRESENTING WITH SCROTAL MASS: POSSIBILITY OF MISINTERPRETATION OF FINDINGS AT AUTOPSY ESPECIALLY IN CUSTODIAL DEATH & ITS MEDICOLEGAL IMPLICATIONS - Kumar, Arvind; Singh, Rishabh Kumar; Kumar, Mahesh (Journal of Forensic Medicine and Toxicology, 2019)
Lack of proper clinical knowledge and their co relation with the autopsy findings can many a times lead to misleading opinion inadvertently. A known case of DM Type I, on medications, regular insulin, on entering the jail his primary health screening which is done in routine for every person entering in the jail was done which came out to be apparently healthy with no external injuries over the body. On subsequent day he became ill presented to OPD Jail, with blood sugar level of 269 mg% with signs of Diabetic Ketoacidosis with shock. He was immediately referred and admitted to a higher multi specialty private medical institute for further management. The condition got deteriorated and he could not be revived and declared dead. After perusal of all the documents and reports the concerned autopsy surgeon opined the final cause of death as Shock and Hemorrhage as result of retroperitoneal hematoma caused by hard blunt object with evidence of lung tuberculosis and acute tubular necrosis.
Keywords: Diabetic ketoacidosis; Shock; Hemorrhage; retroperitoneal hematoma; blunt trauma